1975
DOI: 10.1161/01.res.36.4.547
|View full text |Cite
|
Sign up to set email alerts
|

In vitro acetylcholine biosynthesis in normal and failing guinea pig hearts.

Abstract: Choline acetyltransferase activity, which is rate limiting in acetylcholine biosynthesis, was measured in the four heart chambers of guinea pigs subjected to (1) sham surgery, (2) constriction of the ascending aorta, (3) constriction of the descending thoracic aorta, and (4) constriction of the pulmonary artery. After 30 days when hypertrophy and heart failure were fully established, choline acetyltransferase was quantified in vitro by a radiochemical assay. In the sham-operated group, enzyme activity expresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
3

Year Published

1977
1977
1988
1988

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 11 publications
1
11
3
Order By: Relevance
“…However, in a model of total cardiac denervation, where sympathetic denervation is more complete than in this heart failure model, we detected only a 20% decrease in muscarinic receptor density (24). Furthermore, in terms of the parasympathetic system, Roskoski et al (25) have previously reported in an experimental model of heart failure in the guinea pig, that parasympathetic innervation as assessed by choline acetyl transferase levels, was reduced per unit weight, but not reduced in the entire ventricle. Their findings parallel our observations for muscarinic receptor density, which was reduced per milligram protein in the current investigation, but was not reduced in the entire ventricle, since hypertrophy had almost doubled the ventricular weight.…”
Section: Resultscontrasting
confidence: 51%
“…However, in a model of total cardiac denervation, where sympathetic denervation is more complete than in this heart failure model, we detected only a 20% decrease in muscarinic receptor density (24). Furthermore, in terms of the parasympathetic system, Roskoski et al (25) have previously reported in an experimental model of heart failure in the guinea pig, that parasympathetic innervation as assessed by choline acetyl transferase levels, was reduced per unit weight, but not reduced in the entire ventricle. Their findings parallel our observations for muscarinic receptor density, which was reduced per milligram protein in the current investigation, but was not reduced in the entire ventricle, since hypertrophy had almost doubled the ventricular weight.…”
Section: Resultscontrasting
confidence: 51%
“…20 Also, the group with left heart failure produced by constriction of the ascending aorta, LHF A , was analogous to the experimental guinea pig models reported by Gertler, 21 Schwartz and Lee, 22 and Spann and co-workers. 23 The weights of the left ventricles plus septum and the weights of right ventricles were almost identical to those reported for a guinea pig model of left heart failure by Spann et al 23 In agreement with Spann and co-workers, 23 our preparations with left heart failure also exhibited modest right ventricular enlargement.…”
Section: Vascular Resistance In Heart Failure/sc/i/md Et Alsupporting
confidence: 65%
“…There is extensive evidence confirming parasympathetic innervation of the mammalian ventricle as demonstrated by choline acetyltransferase activity, the presence of ACh, and muscarinic cholinergic receptors (55)(56)(57)(58)(59). However, there are conflicting data regarding the importance of direct vagal effects in the ventricular myocardium and the HPS.…”
Section: Autonomic Effects On the Hpsmentioning
confidence: 99%